Las fuentes del relato de la invasión de los almujuces en la Estoria de Espanna de Alfonso X el Sabio - Francisco Javier González García (Mélanges de la Casa de Velázquez, 2012)
This article examines the sources used to write the passage devoted by Alfonso X’s Estoria de España to the advent of the Almujuces in the Iberian Peninsula and to the formation of their dominion (chapters 14 and 15). The purpose of the article is to explain the use of the sources and the procedures followed in the drafting and composition of this passage by Alfonso’s historiographic workshop. Contrary to the generally-accepted hypothesis that posits the existence of an earlier version, passed on in a now-lost, probably Arab work, the theory proposed here is founded on an acknowledgement of the creative capacity of the historians in Alfonso X’s workshop, sufficient to take sundry materials—among them certain oral traditions and accounts from Ximénez de Rada’s Historia Arabvm or his sources—and so compose the essential part of the account contained in the two chapters of the Estoria d’Espanna.